2017
DOI: 10.1103/physreva.95.033829
|View full text |Cite
|
Sign up to set email alerts
|

Controlling of blow-up responses by nonlinear PT -symmetric coupling

Abstract: We investigate the dynamics of a coupled waveguide system with competing linear and nonlinear loss-gain profiles which can facilitate power saturation. We show the usefulness of the model in achieving unidirectional beam propagation. In this regard, the considered type of coupled waveguide system has two drawbacks, (i) difficulty in achieving perfect isolation of light in a waveguide and (ii) existence of blow-up type behavior for certain input power situations. We here show a nonlinear PT symmetric coupling t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The model ( 15) includes our dimer (2) as a particular case with α = β = 0. However, the integrals of motion of ( 15) do not persist as β → 0; see Ref [19].…”
Section: Related Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model ( 15) includes our dimer (2) as a particular case with α = β = 0. However, the integrals of motion of ( 15) do not persist as β → 0; see Ref [19].…”
Section: Related Systemsmentioning
confidence: 99%
“…The literature suggests several recipes for preventing the blow-up in dimers, including linear vs nonlinear gain-loss competition [18,19] and nonlinear gain-loss saturation [12,20]. This paper explores cross-stimulation-an alternative mechanism that, in addition to ensuring nonsingular evolution, conserves the norm |u| 2 + |v| 2 (interpreted as the total power of light in the optical context).…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical studies [11,12] and experimental realizations [13] have been reported in such systems. PT −symmetry breaking is also an important physical phenomenon because some of the desired properties are achieved at the point of symmetry breaking [14] and in the symmetry broken phase [15,16,17]. Theoretical studies on existence of stable soliton solutions in non−PT symmetric systems are also reported [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In nonlinear optical devices the complex refractive index constitutes the PT −symmetric potential which balances the loss and gain of optical pulse in the medium. PT −symmetry breaking is also an important physical phenomenon because some of the desired properties are achieved at the point of symmetry breaking [9,10] and in the symmetry broken phase [11][12][13][14]. PT −symmetry breaking exploited in many experiments [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of optics, the practicality of inherent loss in any functional device was not considered by the scientific community for many years [26]. But with the advent of parity-time (PT ) symmetry concept, these losses are no longer considered to be detrimental by virtue of the delicate balance between amplification and attenuation [27,28] in the system as in the case of PT -symmetric couplers [29,30], PT -metamaterials [31], PT -microring laser [32], PT -gratings [33,34], PT -laser cavities [35,36], etc. Though this notion traces its origin to the field of quantum mechanics way back in 1998 [37], the translation of the concept on to photonic platform paved the way for its major theoretical advancements [28,38,39] and the first experimental realization by Rütter et al on a LiNbO 3 waveguide [40].…”
Section: Introductionmentioning
confidence: 99%